School of Spectator, Theater as Extension and Citizenship. - Vieira Falabella, Márcia Cristina; de Jesus, Messias Matheus (Guará Journal, 2019)
This  work  intends  to  bring  some  reflections  on  the  experience  of  the  extension  project  School  of  Spectator  executed  in  a  partnership  between  the  Federal  University  of  Juiz  de  Fora  and  the  Center  of  Theater  Studies  -  Grupo  Divulgação.  In  its  32  years  of  operation,  the  project  takes  schools,  centers  and  communities  to  the  Theater,  contributing  to  the  formation  of  spectators  of  working  classes.  We  will make a brief analysis of the participation of the centers attended by the project during the celebrations of the 50 years of Grupo Divulgação, which happened in the first semester of 2016. Student participation was observed during the presentations and their views on the performances. The social themes presented on stage are deepened in  the  classroom,  through  pedagogical  activities  developed  by  students and teachers. The results are positive and point to the contribution of theater to the construction of citizenship.
Keywords: Theater; Citizenship; School of spectator; Divulgação group